ICARE-U Learning Model to Improve Critical Thinking Skills of High School Students in Indonesia - Yenni, Rozi Prima; Siahaan, Parsaoran; Suwarma, Irma Rahma (FKIP Universitas Lampung, 2022)
Critical thinking is one of the skills that are widely trained in the field of natural science studies. The study was conducted at a high school in the city of Padang to determine the effectiveness of ICARE-U learning (Introduction, Connection, Application, Reflection, Extension and Utility) on students' critical thinking skills in the matter of effort and energy. The research method used is pre-experimental with one group pretest posttest design. The research sample consisted of one class 10 high school as many as 31 people. Critical thinking skills are viewed from 5 aspects, namely elementary clarification, basic support, inference, advanced clarification, strategy and tactics. Based on the results of the n-gain on students' critical thinking skills with the ICARE-U learning model, a score of 0.4 was obtained. A score of 0.4 means that students' critical thinking skills before and after being given treatment have increased in the moderate category. Reviewing the critical thinking skills aspect, it is known that the advanced clarification aspect is still experiencing a low increase. Based on the results of hypothesis testing, it was found that the ICARE-U learning model was effectively used to improve students' critical thinking skills in the matter of effort and energy. Keywords: Critical thinking skils, ICARE-U learning model, work and energy. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp585-594